Narrative review: A study of critical points of halalness of milk products and their derivatives - Irena Dwi Mulyaningtias; Aulia Rizki Maulani (Universitas Ahmad Dahlan, 2026)
Dairy products and their derivatives have high nutritional value and are widely consumed, but the complexity of their production processes poses potential risks of non-halal status. Various stages, such as milking, fermentation, enzyme addition, the use of additives, and packaging, can be critical points affecting halal status. This study aims to identify critical points for halal status in milk and dairy products, including yogurt, cheese, butter, ice cream, and probiotic drinks. The study was conducted through a literature review of scientific publications and official documents over the past ten years, focusing on raw materials, processing, additives, and potential contamination. The study results indicate that critical points in raw materials are primarily related to the milk source, its handling, and the hygiene of the process from milking to storage. In fermented products such as yogurt, kefir, and cheese, microbial growth media, starter cultures, and coagulant-forming enzymes are essential aspects that must be verified for halal status. Products such as butter and ice cream may contain critical points, especially in emulsifiers, stabilizers, flavors, colorings, and gelatin, which may be derived from non-halal animal sources. Furthermore, production processes such as pasteurization, ripening, churning, and freezing must ensure there is no cross-contamination with haram ingredients. Overall, identifying and controlling critical halal points at every stage of production is essential to ensure dairy products meet halal principles and are safe for consumption. This study provides a comprehensive mapping guide for the industry to ensure compliance with halal standards and provide assurance to consumers. Keywords: Halal MSMEs, Fishery products, House of risk, Risk mitigation, Supply chain risk.